2016
DOI: 10.1016/j.drugalcdep.2016.07.017
|View full text |Cite
|
Sign up to set email alerts
|

The role of discrimination in alcohol-related problems in samples of heavy drinking HIV-negative and positive men who have sex with men (MSM)

Abstract: Background Heavy drinking is a major public health concern among men who have sex with men (MSM), as it is in many other populations. However, the consequences of heavy drinking among MSM may be particularly severe, especially for sexual risk behavior, due to the relatively high prevalence of HIV. Minority stress models suggest that, among members of marginalized groups, discrimination may be associated with heavier alcohol use as these individuals increasingly drink to cope with such experiences. Past studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 56 publications
1
17
0
1
Order By: Relevance
“…Our prospective data provided partial support for this hypothesis, as we observed a small but statistically significant indirect association from HIV-related stigma at W2 to increased alcohol use severity at W4 mediated by increased maladaptive coping at W3. This finding is consistent with previous studies demonstrating that maladaptive coping mediates the associations of stigma and discrimination with problematic drinking behavior [13,50] although this study is the first to provide a fully longitudinal examination of this pathway and to focus on HIV stigma specifically. Thus, findings suggest that maladaptive coping may be one mechanism linking HIV stigma with alcohol outcomes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our prospective data provided partial support for this hypothesis, as we observed a small but statistically significant indirect association from HIV-related stigma at W2 to increased alcohol use severity at W4 mediated by increased maladaptive coping at W3. This finding is consistent with previous studies demonstrating that maladaptive coping mediates the associations of stigma and discrimination with problematic drinking behavior [13,50] although this study is the first to provide a fully longitudinal examination of this pathway and to focus on HIV stigma specifically. Thus, findings suggest that maladaptive coping may be one mechanism linking HIV stigma with alcohol outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…Further, people living with HIV often endorse using alcohol to cope as one of several motivations for alcohol use, and greater endorsement of using alcohol as a coping strategy correlates uniquely with alcohol problems above and beyond other motives for drinking [34,35]. Moreover, a recent study by Wray et al [13] found that drinking alcohol to cope mediated the relationship between perceived discrimination based on sexual orientation and alcohol problems in a sample of HIV-positive men who have sex with men, suggesting that maladaptive coping plays a role in the link between stigma and alcohol problems in this population. Importantly, this study found that the coping-related pathway from discrimination to alcohol problems was distinct from other motivational pathways such as social or sexual reasons for drinking.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the same study, SRDM were positively associated with an increased frequency of pre-sex drinking over and above general drinking motives (coping, enhancement, and social motives) and sexual alcohol expectancies. Finally, experiencing discrimination among men who have sex with men is associated with SRDM even when coping and enhancement motives were included in the model (Wray et al, 2016). Given the nascent stage of the literature on SRDM, these studies make important first steps in understanding correlates of SRDM and supporting incremental predictive validity.…”
Section: Sexual Victimization and Drinking Motivesmentioning
confidence: 97%
“…Only three studies that we are aware of have examined SRDM (Kahler et al, 2015;Tubman, Wagner, & Langer, 2003;Wray, Pantalone, Kahler, Monti, & Mayer, 2016). One study found that drinking motives to cope with sex-related distress and to enhance sex were associated with alcohol problems and heavy episodic drinking (Tubman et al, 2003).…”
Section: Sexual Victimization and Drinking Motivesmentioning
confidence: 99%